Modeling the Impact of Diversification of Imports on the Natural Gas Market of Ukraine (Economics and region, 2020)
The tools of quantitative assessment of the level of diversification of imported sources and routes of natural gas supply are proposed, the level of diversification of the gas market of Ukraine is assessed, priority ways to increase the level of diversification of the natural gas market of Ukraine in the context of integration into the EU natural gas market are identified. Based on the proposed conceptual and methodological approach to assessing the level of diversification of the natural gas market of Ukraine, a model of diversification of the natural gas market of our country has been developed.Energy security is a timely, complete and uninterrupted supply of fuel and energy of the required quality of material production, non-productive sphere, population, utilities and other consumers; prevention of harmful effects on the environment; transportation, transformation and consumption of fuel and energy resources in the conditions of modern market relations, tendencies and indicators of the world energy market. Ukraine considers own energy security in the context of enhanced cooperation with the EU in the energy sector. Ukraine seeks to implement or expand projects to diversify natural gas supplies, strengthen its status as a reliable transit country, and integrate into the EU's energy space. As part of a targeted policy to diversify natural gas sources, Ukraine cooperates with European operators of related gas transmission systems on the possibility of signing a «cooperation agreement» at all connection points, as well as providing and expanding technical capabilities for gas transportation from Europe. Significant capacity of gas storage facilities in Ukraine in this case can be used for seasonal price arbitrage to reduce the total cost of imported gas.
Keywords: evaluation; mechanism efficiency; reverse gas supply; contract; natural gas transportation; energy independence; economy